Ownership structure and corporate performance : evidence from real estate Industry in Malaysia / Nur Asyilla Jamaludin - Jamaludin, Nur Asyilla (Faculty of Business Management, 2017)
This research is performed to investigate the impact of ownership structure towards the corporate performance. This study is conducted in real estate industry in Malaysia to understand more on how the ownership structure affecting the chosen industry. The dependent variables which is firm performance is tested in several ways towards the independent variables which is government ownership, firm ownership, leverage and firm size. The research would like to compare the performance of a company that have a huge volume of either one of the chosen ownership structure. Therefore, the research would like to see the comparison performance of the real estate industry. This is due to the belief in community that companies that have a huge amount of government ownership tends to perform poorly. The study use panel data regression to test the ownership structure towards the performance of a company. The samples used for this study is 6 real estate companies in Malaysia. The samples are used to investigate for 7 conservative years (2010-2016) of financial report mainly from Bursa Malaysia, Datastream and the companies' website itself. The analysis is based on secondary data and hypothesis testing conduct to determine the relationship between banks performance and all independent variables. Variables which is government ownership and firm performance are expected to have negative significant relationship. Leverage and firm size are expected to have a positive significant relationship with performance of a company.